PREVALENCE OF DEPRESSION, ANXIETY, STRESS IN INDONESIAN FEMALE STUDENTS: LITERATURE REVIEW - Callista, Syadia; Nabilla, Astika; Kayla, Fatimah (Universitas Muhammadiyah Ponorogo, 2026)
The cause of depression, anxiety, and stress in female students is due to the burden of the lecture and academic environment to get the best grades. The purpose of this article is to add the scientific treasure trove regarding the prevalence of depression, anxiety, and stress in Indonesian female students. This type of research is a literature study obtained from scientific articles that are searched using the keywords Anxiety, Depression, Indonesia, Students, Students, Stress, and Prevalence through Google Scholar, PubMed, Science Direct and Research Gate. The criteria for the article used have been published for 10 years, namely 2015-2025, the title and content of the journal are in accordance with the title of the research. The results of the analysis from 23 articles showed that most of the respondents were female students with higher levels of depression, anxiety, and stress than men.